Microbiological quality of minimally processed vegetables commercialized in Brasilia, DF, Brazil - CRUZ,Mariana Rodrigues Gomes da (2019)
Abstract This study evaluated the microbiological quality of minimally processed vegetables commercialized in the city of Brasilia, DF, Brazil. A total of 32 samples of different vegetables were purchased from 10 supermarkets. In most samples (78.1%) the populations of psychrotrophic bacteria had a high count ranging from 106 to 108 CFU/g. Thermotolerant coliforms were found in all samples, with populations higher than 102 MPN/g in 15 samples (46.9%). After molecular analyses, E. coli was identified in 16 samples (50.0%) and Salmonella spp. in 4 samples (12.5%). S. aureus was found in 14 samples (43.8%), with counts higher than 103 CFU/g in 4 samples (12.5%). The results obtained in this study showed that 16 samples (50%) were unfit for consumption according to Brazilian legislation. These results indicated the need of adoption of better hygienic practices in the production of minimally processed vegetables to improve quality and microbiological safety.